Role of Information Sources for Community Development among Poultry Farmers in Ikpoba-Okha Local Government Area of Edo State, Nigeria - Osabuohien, Julius I.; Okoedo-Okojie, D. U. (NIU Journal of Social Sciences, 2026)
This study assessed the role of information sources utilization for community development among poultry farmers in Ikpoba-Okha Local Government Area of Edo State. The specific objectives were to determine the socio-economic characteristics of the farmers in the study area, examine the level of availability of proven poultry technologies to the farmers, identify information sources through which farmers receive technologies. A multi-stage sampling techniques was used to solicit respondents from 120 poultry farmers with questionnaire. Data were analysed using frequency counts, percentages and means while hypothesis were test using PPMC and Chi-Square. Result showed that majority (57.5%) were males, most (81.7%) were married and a higher proportion (45.0%) stocked broilers. The most available technology to respondents was breed of a day-old chicks (=3.82). The highest perceived role of information sources was (=3.55). The most serious constraint faced by respondents was that the extension agent do not teach them at their levels. Household size (r=0.351) had significant association with their roles. It was thus recommended that farmers should be encouraged to form cooperative societies for easy access to credit facility and inputs so as to enhance their productivity level. Keywords: Information Source, Community Development, Poultry Farmers, Ikpoba-Okha